Consumption-Savings Decisions under Upward Looking Comparisons: Evidence from Germany, 2002-2011 - Moritz Drechsel-Grau; Kai Daniel Schmid (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2013)
In this paper we demonstrate that interpersonal comparisons do not only influence people's level of utility but also lead to "keeping up with the Joneses"-behavior as reference consumption substantially affects households' consumption-savings decisions. By applying the insights from the literature on self-reported well-being to the analysis households' economic decisions, we estimate the causal effect of changes in reference consumption, defined as the consumption level of all households who are perceived to be richer, on households' savings and consumption. Using annual household data from the German Socio-Economic Panel (SOEP) for the years 2002 through 2011 allows us to control for various sources of unobserved heterogeneity. We find that when controlling for changes in own income, increases in reference consumption lead to lower savings and increased consumption as predicted by the Relative Income Hypothesis. Furthermore, households in the (upper) middle class of the income distribution are most strongly affected. An increase in reference consumption of 100 euros induces an average reduction of household savings of 10 to 25 euros depending on the household's position in the income distribution. The economic implications of such behavior are particularly helpful for understanding the link between changes in income inequality and developments in aggregate household savings and consumption. Our model attributes between 30 and 40 percent of the variation in changes of household savings to inequality changes.
urn:nbn:de:101:1-201403119271
Keywords: D12; D11; E21; C23; 330; Household Savings; Household Consumption; Interdependent Preferences; Reference Consumption; Relatice Income Hypothesis; Income Inequality